The mistress and the key [large type] - Mezrich, Ben, 1969- (Grand Central Large Print, 2024)
Card shark Hailey Gordon and ex-con Nick Patterson find themselves in Philadelphia, immersed in the history of Benjamin Franklin and Paul Revere. The Liberty Bell, Charles Willson Peale's Museum, and the Tomb of The Unknown Revolutionary Soldier are connected to Franklin in amazing ways. The more they discover, the more shocking the implications become.